Feeling better while waiting: The influence of intrinsic cues of hospital lobby in Portugal and South Korea - Loureiro, S. M. C.; Ferreira, E.S.; Lopes, R.; Jin, K. N. (Proceeding of the 2015 MAG Scholar Global Business, Marketing and Tourism Conference, 2015)
This study aims to explore the effect of three factors of Servicescape on customers’ emotion, perceived quality and image. The proposed model was tested in medical tourism context in Portugal and S. Korea, using a sample of 359 fully completed questionnaires. Findings reveal that ambient and design are the most important factors in formation Servicescape itself in the case of Portugal hospitals and design and social factors in the case of S. Korea hospitals. Servicescape is an effective antecedent of customer image, perceived quality and pleasure-feeling. Finally, the article also provides managerial implications and suggests avenues for further research.